Molecular Docking Analysis of Anti-dengue Activity of Moringa oleifera Leaves Bioactive Compounds - Riwu, Audrey Gracelia; Jannah, Insani Fitrahulil; Riwu, Katty Hendriana Priscilia; Kale, Maria Laurenci Fanny Permata; Loe, Fhady Risckhy; Asa, Halena Meldy (Universitas Nusa Cendana, 2024)
Background: Dengue infection is an endemic disease in various tropical regions, including Indonesia, with increasing incidence and mortality rates, and currently, no specific therapy is available. One of the potential targets for therapeutic development is the dengue virus (DENV) envelope (E) protein, which plays a crucial role in viral replication in the host. Objective: This study aimed to explore the potential of bioactive compounds from Moringa oleifera leaves as inhibitors of the E protein through an in silico approach using molecular docking methods. Methods: A total of 17 bioactive compounds from Moringa oleifera leaf extract, based on previous studies, were obtained from the PubChem database, while the target protein structure was retrieved from the Protein Data Bank (RCSB). The drug-likeness properties of the compounds were evaluated using the SwissADME web tool. Molecular docking analysis was performed using PyRx Autodock, followed by 3D visualisation and ligand–protein interaction analysis using PyMOL and Discovery Studio 2.0. Apigenin, chrysin, kaempferol, and quercetin exhibited more negative binding affinity values than the control compound Celgosivir (-6.2 kcal/mol), with respective values of -7.4, -7.3, -7.4, and -7.3 Results: kcal/mol. These compounds also shared key amino acid residues with the control at the active site of the envelope protein. Moreover, all four compounds fulfilled the five drug-likeness criteria, indicating good oral bioavailability. Conclusion: Moringa oleifera leaves show potential as candidate anti-dengue agents through inhibition of the DENV envelope protein. Keywords: Moringa oleifera, molecular docking, dengue, antiviral, envelope protein